EXPLORING WHEAT AND BARLEY-BASED TECHNIQUES IN YOGURT PRODUCTION - I.R. Askarov; D.T. Khasanova (Western European Studies, 2024)
This article delves into the pivotal chemical parameters influencing the nutritional quality of harvested grains, with a specific focus on wheat and barley. Recognizing the fundamental role of these grains in the culinary landscape, the study explores their potential to enhance the nutritional profile of yoghurt production. Emphasizing an innovative approach, the article sheds light on the advantages derived from utilizing harvested wheat and barley grains, particularly when subjected to malt treatment with UV rays. The synergy between grain characteristics and ultraviolet treatment is dissected to showcase its transformative impact on yoghurt manufacturing. Insights into key chemical components contribute to a comprehensive understanding of how these grains can elevate the nutritional value of the final yoghurt product, paving the way for advancements in the field of grain-based yoghurt production.
Keywords: harvested wheat; barley; malt; Harvested grains